A long-acting PAI-1 inhibitor reduces thrombus formation - Peng, Shuangzhou; Xue, Guangpu; Gong, Lihu; Fang, Chao; Chen, Jingfei; Yuan, Cai; Chen, Zhuo; Yao, Lishan; Furie, Bruce; Huang, Mingdong (Thrombosis and Haemostasis, 2017)
Plasminogen activator inhibitor 1 (PAI-1) is the main inhibitor of tissue-type and urokinase-type plasminogen activators (t/uPA) and plays an important role in fibrinolysis. Inhibition of PAI-1 activity prevents thrombosis and accelerates fibrinolysis, indicating that PAI-1 inhibitors may be used as effective antithrombotic agents. We previously designed a PAI-1 inhibitor (PAItrap) which is a variant of inactivated urokinase protease domain. In the present study, we fused PAItrap with human serum albumin (HSA) to develop a long-acting PAI-1 inhibitor. Unfortunately, the fusion protein PAItrap-HSA lost some potency compared to PAItrap (33 nM vs 10 nM). Guided by computational method, we carried out further optimisation to enhance inhibitory potency for PAI-1. The new PAItrap, denominated PAItrap(H37R)-HSA, which was the H37R variant of PAItrap fused to HSA, gave a six-fold improvement of IC50 (5 nM) for human active PAI-1 compared to PAItrap-HSA, and showed much longer plasma half-life (200-fold) compared to PAItrap. We further demonstrated that the PAItrap(H37R)-HSA inhibited exogenous or endogenous PAI-1 to promote fibrinolysis in fibrin-clot lysis assay. PAItrap(H37R)-HSA inhibits murine PAI-1 with IC50 value of 12 nM, allowing the inhibitor to be evaluated in murine models. Using an intravital microscopy, we demonstrated that PAItrap(H37R)-HSA blocks thrombus formation and platelet accumulation in vivo in a laser-induced vascular injury mouse model. Additionally, mouse tail bleeding assay showed that PAItrap(H37R)-HSA did not affect the global haemostasis. These results suggest that PAItrap(H37R)-HSA have the potential benefit to prevent thrombosis and accelerates fibrinolysis.
Keywords: PAI-1 inhibitor; human serum albumin (HSA); thrombosis; clot lysis